Repeat procedures and reconnection rates after cryoballoon PVI with phrenic nerve injury. (19th May 2022) - Heeger, CH; Sohns, C; Pott, A; Metzner, A; Inaba, O; Straube, F; Kuniss, M; Aryana, A; Miyazaki, S; Chun, JC; Kuck, KH; Dahme, T; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Aims: Cryoballoon (CB) based pulmonary vein isolation (PVI) is an effective treatment for atrial fibrillation (AF). The most frequent complication during CB-based PVI is right-sided phrenic nerve injury which is leading to premature abortion of the freeze cycle. Here we analysed repeat procedures and reconnection rates after CB-based PVI and phrenic nerve injury in a large-scale population. Due to the fact that the freezing process was prematurely interrupted the data may offer unique findings in optimizing the CB dosing protocols. Methods and Results: In the YETI registry a total of 17356 patients underwent CB-based PVI in 33 centers and 731 (4.2%) patients experienced phrenic nerve injury. A total of 111 / 731 (15.2%) patients received a repeat procedure utilizing a 3D mapping system due to AF recurrence. In 94/111 (84.7%) of patients data on repeat procedures was available. During their initial PVI procedures, phrenic nerve injury occurred during treatment of RSPV (n=80), RIPV (n=13) and LSPV (n=1). A total of 89/94 (94.7%) target PVs have been isolated during the initial PVI (RSPV: 75/80, 94%; RIPV: 13/13; 100%; LSPV: 1/1; 100%). The mean freezing time was 127±46s and the mean minimal temperature was -49±7°C. During the repeat procedures 67 of initially 89 isolated PVs showed persistent isolation (75%, for RSPV: 55/75; 73%; RIPV: 11/13; 85%; LSPV: 1/1; 100%). Conclusion: In patients initially treated by CB-based PVI with interruption of the freezing due to phrenic nerve injury, a high rate of durable isolated PVs has been detected at repeat procedures. Our data may help to identify the optimal dosing protocol in CB-based PVI procedures